Therapist verbal behavior in the multidimensional system for coding behaviors in therapeutic interaction (SiMCCIT) - Zamignani, Denis; Meyer, Sonia Beatriz (Perspectivas em Análise do Comportamento, 2017)
Therapeutic interaction has been considered one of the main factors of change in psychotherapy, and its investigation is called process research. Audio and video recording sessions are used to code behaviors which, subsequently, permit the analysis of interaction patterns. The objectives of the study were the presentation of part of a coding system called “Multidimensional System for Categorization of Behaviors in Therapeutic Interaction” and the evaluation of agreement between observers in its use. From a systematic assessment of the literature regarding the classification of vocal verbal behavior, it was found that the existing category systems were not satisfactory for the study of behavior analytic therapy, thus requiring the construction of a new system. A System for Coding Verbal Therapist Behavior was developed containing 16 categories, nine of vocal verbal behavior, three for non-vocal verbal behavior and four residual categories. A standardized training for observers was also developed. Its application to one participant produced satisfactory Kappa indexes of agreement ranging from 0.67 to 0.84. The implications of using the system for process research in behavior analytic therapy and in other therapeutic modalities in its different stages are discussed as well as the possibility of using the instrument and its training software for teaching therapeutic skills.